The Development and Implementation of Game-based learning for Tasawwur Islam Subject: Insights from Teachers and Classroom Integration - Zulkefli, Murni; Jamil, Asyraf Isyraqi (Journal of Islamic Educational Research, 2025)
This study explores the integration of game-based learning to enhance the teaching and learning of Tasawwur Islam, focusing on student engagement, motivation, and retention of complex Islamic concepts. Using a qualitative approach, Focus Group Discussions (FGDs) were conducted with nine Tasawwur Islam teachers, complemented by classroom case studies in six schools. FGDs provided insights into teachers' perspectives on the challenges of teaching abstract concepts, while case studies assessed the practical impact of gamification on student learning outcomes. The findings revealed that mobile-based games significantly improved student engagement, particularly among underperforming students (GALUS) who typically struggle with traditional teaching methods. These students, often kinesthetic learners, benefited from the interactive and movement-oriented nature of gamified tools. Furthermore, tools like Tarsia Istilah and Quizizz enhanced memory retention of Islamic terminologies. Gamified tools also provided real-time feedback, enabling teachers to adapt their instructional strategies continuously. However, while game-based learning offer many benefits, balancing these with traditional teaching methods is essential to ensure deeper conceptual understanding. This study contributes to the growing body of research on Islamic education by demonstrating the potential of game-based learning to create more interactive, engaging, and effective learning experiences.